2022
DOI: 10.3390/f13020143
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Protocol Design for Suitable Green In Situ Synthesis of ZnO on Cotton Using Aqueous Extract of Japanese Knotweed Leaves as Reducing Agent

Abstract: This work presents two protocols for the green in situ synthesis of zinc oxide nanoparticles (ZnO-NP) on cotton with the aim to develop sustainable cotton fabric with an ultraviolet protection factor (UPF). The protocols differed in the order of immersing cotton fabric in reactive solutions of three batches, i.e., precursor (0.1 M zinc acetate dihydrate), reducing agent (aqueous extract of Japanese knotweed leaves) and alkali (wood ash waste). The scanning electron microscope (SEM) results showed that ZnO-NP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
0
15
1
Order By: Relevance
“…Moreover, it was discovered that the sequence of synthesis solutions is crucial to obtain small and uniformly distributed ZnO particles [7]. Based on the obtained results, this study presents the implementation of the suitable in situ ZnO synthesis protocol described in Verbič et al 2022 [7] on a new textile substrate. The synthesis was performed by immersing samples in three synthesis solutions: natural alkaline medium, zinc precursor and natural reducing agent.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, it was discovered that the sequence of synthesis solutions is crucial to obtain small and uniformly distributed ZnO particles [7]. Based on the obtained results, this study presents the implementation of the suitable in situ ZnO synthesis protocol described in Verbič et al 2022 [7] on a new textile substrate. The synthesis was performed by immersing samples in three synthesis solutions: natural alkaline medium, zinc precursor and natural reducing agent.…”
Section: Introductionmentioning
confidence: 90%
“…However, it was soon realised that fully green syntheses performed directly on a textile substrate are not easily achievable, and the use of classical reducing agents and solvents was often further pursued in addition to the natural extract. There are only a few published studies in which green in situ synthesis was performed directly (in situ) on a textile substrate using only natural aqueous extracts [6][7][8], without any chemicals acting as an alkaline medium or reducing agent. However, those syntheses were performed on cotton fabrics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, both classical and plant-derived reducing agents have been used for the in situ synthesis of nanoparticles on textiles [14,15]. Moreover, it was shown that classical reducing agents are not necessary when synthesis methods with the proper design are used [16,17]. Pomegranate peels were found to be a great reducing agent for the synthesis of various nanoparticles [18][19][20].…”
Section: Introductionmentioning
confidence: 99%